Boundaryless careers - Anne-Françoise BENDER; Cécile DEJOUX; Heidi WECHTLER (Revue de Gestion des Ressources Humaines, 2009)
According to research on Boundaryless careers (i.e. careers characterised by inter-firm mobility and/or professional changes), mobile professionals should develop specific career planning competencies, especially networking (Knowing-Who) and Self-knowledge skills (Knowing-Why). This hypothesis was tested in a survey answered by 177 adults enrolled in continuing education programs. The quantitative analysis of results of the survey highlights the existence of relationships between Boundaryless career orientations, Career planning competencies (Knowing) and Emotional skills, the latter including networking and selfknowledge skills. As anticipated, results reveal relationships between “Reconversion” career orientations (people who are eager to change professions), Knowing-Who skills and a Dimension of Schutte’s EI scale regarding the “Emotional Regulation of Others”. This career orientation is also significantly more feminine than the others. In addition, the less mobile career orientation group (named “Specialists”) is characterised by significantly lower scores on the EI dimension “Utilization of Emotions in Problem Solving”. However, some other Boundaryless career orientations (“Intra-firm mobile” and “Self-Employment”) also record low scores on certain EI dimensions. These results thus point that the fact relationships between Boundaryless Careers, Knowing and Emotional Intelligence need further exploration.